2018
DOI: 10.1242/bio.030981
|View full text |Cite
|
Sign up to set email alerts
|

Low cholesterol is not always good: low cholesterol levels are associated with decreased serotonin and increased aggression in fish

Abstract: The inverse relationship between serum cholesterol and levels of aggression led to the cholesterol-serotonin hypothesis. According to this hypothesis, low dietary cholesterol intake leads to depressed central serotonergic activity, which is associated with increased aggression. Here we present the hypothesis about the evolutionary origins of low cholesterol and aggressive behavior, investigating the relationship between low levels of plasma cholesterol and aggressive behavior in fish. We used Nile tilapia (Ore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
9
2
Order By: Relevance
“…In an interesting study designed to evaluate the neurobiological basis of aggressive behavior, it was demonstrated that in Nile tilapia, a fish with a belligerent behavior, atorvastatin treatment reduces plasma cholesterol and the telencephalic ratio between the main serotonin metabolite, 5-HIAA, and serotonin, and increases aggressive behavior compared to control fish [63]. These observations suggest that modification of plasma cholesterol may impact on the neurochemical mechanisms responsible for the belligerent tilapia behavior, pointing to the possibility that this mechanism is conserved in the phylogeny of vertebrates.…”
Section: Neurotransmitter Levelsmentioning
confidence: 99%
“…In an interesting study designed to evaluate the neurobiological basis of aggressive behavior, it was demonstrated that in Nile tilapia, a fish with a belligerent behavior, atorvastatin treatment reduces plasma cholesterol and the telencephalic ratio between the main serotonin metabolite, 5-HIAA, and serotonin, and increases aggressive behavior compared to control fish [63]. These observations suggest that modification of plasma cholesterol may impact on the neurochemical mechanisms responsible for the belligerent tilapia behavior, pointing to the possibility that this mechanism is conserved in the phylogeny of vertebrates.…”
Section: Neurotransmitter Levelsmentioning
confidence: 99%
“…Kaplan et al introduced the cholesterol-5-HT hypothesis, stating that lowered cholesterol levels from poor diet or inhibited synthesis might result in reduced central 5-HT activity. This theory provides some insight into cholesterol’s role in depressive behavior, suicidal tendencies, and aggressiveness. It has been suggested that low cholesterol and 5-HT levels make men more prone to violent behavior and risk-taking compared to women …”
Section: Lipid Effects On 5-ht Throughputmentioning
confidence: 99%
“…265 Statins, medications that hinder cholesterol synthesis and lower plasma levels, reduce the telencephalic 5-HIAA/5-HT ratio in Nile tilapia fish and decrease the 5-HT brain levels in rodents. 261,266 Meanwhile, treatment with antidepressants like paroxetine, clomipramine, sertraline, duloxetine, and fluoxetine, which have strong SERT affinity, leads to higher LDLcholesterol levels. 266 While there is a definitive link between cholesterol and 5-HT function, the exact process remains unknown.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Psychological correlates of aggression including emotion, motivation, cognitive functions, and behavior are driven and nourished by extensive neural pathways and neuroendocrine mechanisms (74).…”
Section: Neurobiological and Lipidergic Correlates Of Other-directed And Self-directed Aggressive Behaviormentioning
confidence: 99%
“…Similar to impulsivity, serotonergic neurotransmission is the most-studied neural function in the physiology of aggression (74). In recent decades, it has been shown that there is an inverse relationship between serotonin concentrations in the synaptic cleft in the brain and the expression of aggressive behavior (75).…”
Section: Neurobiological and Lipidergic Correlates Of Other-directed And Self-directed Aggressive Behaviormentioning
confidence: 99%